The Affective consequences of expected and unexpected outcomes - Shepperd, James A.; McNulty, James K. (2002)
How do people feel about unexpected positive and negative outcomes? Decision affect theory (DAT) proposes that people feel displeasure when their outcomes fall short of the counterfactual alternative and elated when their outcomes exceed the counterfactual alternative. Because disconfirmed expectations provide a counterfactual alternative, DAT predicts that bad outcomes feel worse when unexpected than when expected, yet good outcomes feel better when unexpected than when expected. Consistency theories propose that people experience displeasure when their expectations are disconfirmed because the disconfirmation suggests an inability to predict. According to consistency theories, both good and bad outcomes feel worse when unexpected than when expected. These two theoretical approaches were tested in three studies. The results consistently support DAT